Lateral facies heterogeneity and carbonate productivity changes during the Lower Jurassic of the Traras Mountains (NW Algeria): local versus regional controls - Belkhedim, Salim; Munnecke, Axel; Benaaoume, Hachemi Mokhtar; López Correa, Matthias; Nemra, Abdelkrim; Bradai, Mohammed El Amine; Benhamou, Miloud (Facies, 2025)
Lateral facies heterogeneity and carbonate production perturbation within peri-Tethyan platforms were widespread phenomena during the Early Jurassic. These variations were either controlled by local factors affecting small areas or by processes prevailing on a global scale. Three geological sections are investigated in Lower Jurassic outcrops in the Traras Mountains, northwest Algeria, from synrift-settings to disentangle the influence of local and global factors. The detailed sedimentological study reveals 11 facies types, grouped into four facies associations ranging from alluvial fan to outer ramp setting. Whereas thickness variation and lateral facies distribution are mainly controlled on a regional scale by synsedimentary tectonics, resulting from the spreading of the Tethys, the irregular topography inherited from the palaeo-alluvial fan topography of the underlying Beni Menir Formation seems to be the main control on a local scale. This irregular topography which coexisted in very close proximity to the studied carbonate deposits provided a significant amount of siliciclastic input, partially disturbing carbonate production. The local erosion of this detrital material during the initial early Pliensbachian transgression, combined with other local factors such as a low rate of accommodation space renewal and high-energy conditions, resulted in the absence of the otherwise prevalent Lithiotis fauna in the studied sector. Siliciclastic input perturbating carbonate production during the late Pliensbachian to early Toarcian could instead have been induced by a global warming event that increased continental weathering at the global scale during the Pl/To boundary or T-OAE associated with storm intensification. Alternatively, in view of the lack of solid biostratigraphic attribution, high terrigenous input could also have been induced from a cooling event leading to a sea-level fall during the latest Pliensbachian (Emaciatum Zone) and/or the lowermost Toarcian (latest Tenuicostatum Zone). In addition to tectonics, this eustatic sea-level fall could also explain the absence of shallow carbonate production in the Traras Mountains during these periods. In the future, a multidisciplinary basin-scale approach may resolve these uncertainties related to the lack of biostratigraphic dating, thus helping to identify the key factor influencing the perturbation of carbonate production.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Climate change; Eustatic sea-level change; Facies analysis; Jurassic Algeria; Synsedimentary tectonics; Traras Mountains